Efek Digital Work Environment terhadap Innovative Work Behavior: Peran Mediasi Employee Engagement dan Moderasi Work Distress pada UMKM Kuliner Surabaya - Anita Asnawi; Sri Utami Ady (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
In the era of digital transformation, small businesses increasingly depend on technology to enhance efficiency and foster innovation. This study investigates how digital work environments (DWE) influence innovative work behaviour (IWB) among employees of culinary MSMEs in Surabaya, Indonesia, with employee engagement (EE) as a mediator and work distress (WD) as a moderator. Based on the Job Demands–Resources (JD–R) framework, data from 156 respondents were analyzed using SmartPLS 3. Results show that DWE strongly promotes EE, which subsequently drives IWB, confirming partial mediation. However, DWE has no direct effect on innovation, indicating that digital systems stimulate creativity mainly through psychological engagement. WD negatively affects innovation but does not moderate the EE–IWB link. These findings illustrate a dual mechanism within JD–R theory, where digital environments act as motivational resources while distress independently hinders creativity. The study enriches understanding of JD–R dynamics in digitalized MSMEs and highlights the importance of balancing technology, engagement, and well-being to sustain innovation.